2000
DOI: 10.1089/108729100413239
|View full text |Cite
|
Sign up to set email alerts
|

Service Use Patterns of Youth with, and at High Risk for, HIV: A Care Typology

Abstract: This paper uses confirmatory structural equation models to develop and test a theoretical model for understanding the service utilization history of 4679 youth who received services from 10 national HIV/AIDS demonstration models of youth-appropriate and youth-attractive services funded by the Special Projects of National Significance (SPNS) Program, HIV/AIDS Bureau, Health Resources and Services Administration. Although the projects differ from one another in the areas of emphasis in their service models, each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Huba et al (2000) using data from the Special Projects of National Significance Program evaluated several programs that were targeted specifically to youth at high risk for acquiring HIV. Integrated service delivery networks were used to develop differentiated paths of service that occurred among the youth accessing services.…”
Section: Introductionmentioning
confidence: 99%
“…Huba et al (2000) using data from the Special Projects of National Significance Program evaluated several programs that were targeted specifically to youth at high risk for acquiring HIV. Integrated service delivery networks were used to develop differentiated paths of service that occurred among the youth accessing services.…”
Section: Introductionmentioning
confidence: 99%
“…More than half of the 14,000 people newly infected each year are under 25 years of age; most of which are female. However, despite the disproportionate burden youth carry, studies show (Huba et al, 2000) that youth are more likely than adults to adopt and maintain safe behaviors; however, young people are routinely disregarded when strategies on HIV/AIDS are drafted, policies made and budgets allocated (Office of National AIDS Policy [ONAP], 2003). Youth between the ages of 13 and 24 in the United States are at unrelenting risks for HIV infection, particularly youth of minority races and ethnicities (Coyle et al, 2004;CDC, 2010).…”
Section: Hiv Positive Youth and Healthcare Utilizationmentioning
confidence: 99%
“…Healthcare services utilization is of utmost importance in minimizing social support and medical care needs for youth infected with the virus that causes HIV. Research has confirmed the benefits of early diagnosis of HIV/AIDS and the literature regarding health care utilization speaks to a number of studies related to HIV care services utilization for adults (Kellerman et al, 2006;Huba et al, 2000). Conversely, there was a dearth of articles that addressed the HIV health care services utilization for HIV positive youth 13 to 24 years of age.…”
Section: Hiv Positive Youth and Healthcare Utilizationmentioning
confidence: 99%